Anticancer activity of synthesized Ag-doped CuO nanoparticles using Ephedra intermedia plant against PC-3 prostate cancer cell line - Prasia Raisi Dehkordi; Azadeh Mohammadgholi; Nastaran Asghari Moghadam (Nanomedicine Journal)
Objective(s): This research was done to synthesize Ag-doped copper (CuO) nanoparticles (NPs) using the Ephedra intermedia plant and investigate its anticancer properties against the PC-3 prostate cancer (PC) cell line.Materials and Methods: Ag-doped-Cu NPs were biologically synthesized using E.intermedia extract. The synthesized Ag-doped-Cu NPs were characterized using X-ray diffraction (XRD), CuK radiation and fourier-transform infrared spectroscopy (FT-IR), dynamic light scattering (DLS), transmission and scanning electron microscopy (TEM and SEM, respectively) as well as energy dispersive X-ray (EDAX).  The expression of Bax, Bcl2, P53, and caspase-3 genes was evaluated by Real-time PCR (RT-PCR) and apoptosis was assayed using Annexin-V kit. Also, the production of reactive oxygen species (ROS) was estimated at 1000 RFU and 1500 RFU in PC-3 cells treated with extract and green-synthesized Ag-doped-Cu NPs.  Results: The particles were in nano size (55.24-84.41 nm) and the XRD test proved the crystalline structure of NPs. EDAX analysis confirmed the presence of Cu, C, and Ag elements. The results of gene expression showed that the IC50 concentration of the doped NPs makes a significant increase in the Bax, caspase-3, and P53 expression levels and a significant decrease in the Bcl2 expression compared to the reference gene and the extract-treated cells. Treatment with doped NPs induced more apoptosis and necrosis than that of treatment with extract. Also, a remarkable enhancement in nitric oxide (NO) enzyme levels was found in the doped NPs compared to the extract alone.Conclusion: This study proves that the doped NPs induce apoptosis by affecting the expression of pro-apoptotic genes and ROS over-production.